Peri-implantation estradiol level has no effect on pregnancy outcome in vitro fertilization- embryo transfer - Huang, Pinxiu; Ou, Yuan; Tang, Ni; Chen, Jing; Wen, Qiuyue; Li, Jingjing; Zeng, Dingyuan (Frontiers in Endocrinology, 2024)
The necessity of monitoring luteal endocrine functions in in vitro fertilization-embryo transfer (IVF-ET) remains uncertain. Specifically, the significance of luteal phase estradiol (E2) levels is a matter of debate in current literature. Objective: To assess the impact of luteal phase (day 11 after HCG trigger) estradiol levels on IVF-ET outcomes. Design: Twelve thousand five hundred and thirty-five (n = 12,535) IVF-ET cycles performed in our center between 2015 and 2021 were divided into 5 groups based on the middle and late luteal phase serum E2 (MllPSE2) level percentiles as follows: Group A < 50 pg/mL (N=500), group B 50 pg/mL≤E2<150 pg/mL (N=2545), group C 150 pg/mL≤E2<250 pg/mL (N=1327), group D 250 pg/mL≤E2<500 pg/mL (N=925), group E E2 ≥500 pg/mL (n=668). The clinical pregnancy rates, abortion rates, and live birth rates of each group were compared. Binary logistic regression analysis was carried out to assess the potential impact of MllPSE2 on the live birth rate (LBR). Results: No significant differences were found in various parameters when comparing the five groups. The level of MllPSE2 showed no significant difference between the pregnant group and the non-pregnant group. The binary logistic regression analysis model demonstrated that MllPSE2 was not significantly related to LBR.The influence of E2 during the peri-implantation period (day 11) on clinical outcome in IVF-ET is not affected, even if E2<50 pg/mL. It is speculated that ovarian-derived E2 in MllPSE2 is not deemed necessary for endometrial receptivity. Although caution is warranted due to the retrospective nature of the analysis and the potential for unmeasured confounding, it is argued that the need for luteal E2 monitoring in IVF-ET may be of questionable value.